Design Alat Monitoring pH Levels Limbah Cair Hasil Tambang Batubara Berbasis Arduino Uno - Wahyu Dwi Reza; Feranita Feranita; Nurhalim Nurhalim (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
In coal mining, to check the pH content of water in liquid waste from coal mining, mining workers mostly use the conventional method, namely by periodically measuring using a digital pH meter or litmus paper. Manual pH reading system makes handling slow. Based on these reasons the research designed a device that can monitor the pH value, the working principle of this tool is that the pH electrode is inserted into the sample solution and then the electrode detects the sample solution and will change the electrical signal where the output will be amplified by an amplifier circuit in the form of an analog voltage and will be converted. by Arduino Uno, analog data is converted into digital data or ADC (Analog To Digital Convertion) so that the results will be displayed on an LCD that is equipped with I2C. And this tool is also equipped with RTC (Real Time Clock) so that it can display the time when data collection on the pH level of the waste. The tool that is designed has an error percentage of the pH meter manufacturer of 0.4969%. By using this tool the authors conclude with 0.4 grams of lime (CaO) on the prototype or 480 kg in real conditions with a ponds area of 600 m3 can reduce the voltage output on the ph sensor from 3.25 V to 2.56 V so that the pH value increases. from 2.73 to 7.61 in pond 4 or dump ponds. Keywords: Coal waste, pH, Arduino Uno, ADC, voltage, chalk (CaO)